Computational fluid dynamics simulation improves the design and characterization of a plug‐flow‐type scale‐down reactor for microbial cultivation processes. Issue 1 (28th November 2022) - Mayer, Florian; Cserjan‐Puschmann, Monika; Haslinger, Benedikt; Shpylovyi, Anton; Sam, Christian; Soos, Miroslav; Hahn, Rainer; Striedner, Gerald
Abstract: The scale‐up of bioprocesses remains one of the major obstacles in the biotechnology industry. Scale‐down bioreactors have been identified as valuable tools to investigate the heterogeneities observed in large‐scale tanks at the laboratory scale. Additionally, computational fluid dynamics (CFD) simulations can be used to gain information about fluid flow in tanks used for production. Here, we present the rational design and comprehensive characterization of a scale‐down setup, in which a flexible and modular plug‐flow reactor was connected to a stirred‐tank bioreactor. With the help of CFD using the realizable k ‐ ε model, the mixing time difference between a 20 and 4000 L bioreactor was evaluated and used as scale‐down criterion. CFD simulations using a shear stress transport (SST) k ‐ ω turbulence model were used to characterize the plug‐flow reactor in more detail, and the model was verified using experiments. Additionally, the model was used to simulate conditions where experiments technically could not be performed due to sensor limitations. Nevertheless, verification is difficult in this case as well. This was the first time a scale‐down setup was tested on high‐cell‐density Escherichia coli cultivations to produce industrially relevant antigen‐binding fragments (Fab). Biomass yield was reduced by 11% and specific product yield was reduced by 20% during the scale‐down cultivations. Additionally, the intracellular Fab fraction was increased by using the setup. The flexibility of the introduced scale‐down setup in combination with CFD simulations makes it a valuable tool for investigating scale effects at the laboratory scale. More information about the large scale is still necessary to further refine the setup and to speed up bioprocess scale‐up in the future. Graphical Abstract and Lay Summary: The heterogenous production conditions in large‐scale bioreactors cause scale‐up problems, such as reduced biomass or product yield, to occur during bioprocesses. In this study, we designed a two‐compartment scale‐down reactor and used it to simulate large‐scale heterogenous production conditions, allowing us to understand these scale‐up problems and identify solutions at the laboratory scale. A computational fluid dynamics simulation was used for the design and detailed characterization of the scale‐down setup, as this simulation can model the production scale and support improved bioprocess scale‐up in the future.